2014
DOI: 10.1016/j.bbamcr.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster cellular repressor of E1A-stimulated genes is a lysosomal protein essential for fly development

Abstract: Mammalian cellular repressor of E1A-stimulated genes is a lysosomal glycoprotein implicated in cellular growth and differentiation. The genome of the fruit fly Drosophila melanogaster encodes a putative orthologue (dCREG), suggesting evolutionarily conserved physiological functions of this protein. In D. melanogaster S2 cells, dCREG was found to localize in lysosomes. Further studies revealed that intracellular dCREG is subject of proteolytic maturation. Processing and turnover could be substantially reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Kowalewski‐Nimmerfall et al. () reported on a Drosophila CREG (dCREG) that localizes to lysosomes. Experiments with gene‐knockout Drosophila lines show ablating the protein is lethal at the late pupal stage, indicating dCREG is essential for development of the fly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kowalewski‐Nimmerfall et al. () reported on a Drosophila CREG (dCREG) that localizes to lysosomes. Experiments with gene‐knockout Drosophila lines show ablating the protein is lethal at the late pupal stage, indicating dCREG is essential for development of the fly.…”
Section: Discussionmentioning
confidence: 99%
“…Mammals express a secreted glycoprotein, cellular repressor of E1A-stimulated genes (CREG) that inhibits E1A-stimulated effects (Yang et al, 2011). Kowalewski-Nimmerfall et al (2014) reported on a Drosophila CREG (dCREG) that localizes to lysosomes. Experiments with gene-knockout Drosophila lines show ablating the protein is lethal at the late pupal stage, indicating dCREG is essential for development of the fly.…”
Section: Discussionmentioning
confidence: 99%
“…CREG is reported to predominantly localize within lysosomes [8][9][10]. Therefore, we investigated the effect of CREG on lysosome function in macrophages.…”
Section: Creg Protein Modulates Lysosomal Maturationmentioning
confidence: 98%
“…Recently, CREG is identified to be a bona fide lysosome protein and undergoes proteolytic maturation by lysosomal cysteine proteases in the course of their biosynthesis [8,9]. Expression of CREG is highest in lymph nodes and monocytes in both human and murine tissues as shown in EST databases on the NCBI-UniGene site.…”
Section: Introductionmentioning
confidence: 97%
“…This suggests that the Man 6-P-dependent sorting mechanism is absent in flies. Most recently, Kowalewski-Nimmerfall et al reported that RNAi knockdown of LERP in S2 cells had only a small effect on the retention of the lysosomal enzyme cathepsin L and no effect on lysosomal CREG (cellular repressor of EIA-stimulated genes retention), leading them to suggest that LERP is not a universal sorting receptor for lysosomal proteins in flies ( Kowalewski-Nimmerfall et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%